2019
DOI: 10.1111/fare.12390
|View full text |Cite
|
Sign up to set email alerts
|

Parental Naming Practices in Same‐Sex Adoptive Families

Abstract: Objective To explore the ways in which same‐sex adoptive parents navigate the process of determining what terms their children will use to address them (i.e., parent names). Background Parent names are markers of familial relationships and identity. Different‐sex parents are linguistically privileged in that their parent names are widely recognizable, easily distinguishable between each parent, and usually assigned by default as opposed to chosen, whereas parents in same‐sex couples must go through a deliberat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Findings also highlight the unique experiences of TNB adoptive parents, in that they had less flexibility over name choice and how their child saw them. Adoptive parents had to consider their child’s understanding of gender and parenting, and the parents already present in their child’s birth family, which echoes previous research in the US with cis same-sex adoptive parents (Frank et al, 2019 ). It has previously been suggested that parental name decision making is easier amongst parents who come out before becoming a parent, than those who come out after becoming a parent (Petit et al, 2017 ), but the findings of the present study highlight that this process may be more challenging in TNB adoptive parent families, regardless of when the parent came out.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Findings also highlight the unique experiences of TNB adoptive parents, in that they had less flexibility over name choice and how their child saw them. Adoptive parents had to consider their child’s understanding of gender and parenting, and the parents already present in their child’s birth family, which echoes previous research in the US with cis same-sex adoptive parents (Frank et al, 2019 ). It has previously been suggested that parental name decision making is easier amongst parents who come out before becoming a parent, than those who come out after becoming a parent (Petit et al, 2017 ), but the findings of the present study highlight that this process may be more challenging in TNB adoptive parent families, regardless of when the parent came out.…”
Section: Discussionmentioning
confidence: 65%
“…This experience points to the way in which participants negotiated and worked with their children’s understandings of gender and parenting (see also Zadeh et al, 2021 ), which may be more established among older children (Frank et al, 2019 ). Birth parents also spoke about considering their child’s needs; Yanniq (a neither gender person) noted that they would “much rather refer to myself as father, at least privately”, but worried that this may be confusing for their child:…”
Section: Resultsmentioning
confidence: 90%
“…Parallel naming practices can powerfully signify parent–child relationships (Frank et al, 2019) and were endorsed by three quarters of parents. Yet such practices are also highly gendered, which may not be desirable for all LGBTQ parents: Indeed, as we documented, TNB parents were less likely to endorse parallel naming.…”
Section: Discussionmentioning
confidence: 99%
“…Almost three quarters of parents said that the child had the same last name as the nonbiological parent, either via a shared family name or by taking the nonbiological parent’s surname. Naming is a powerful way of communicating parent–child relationships, thereby establishing the legitimacy of the nonbiological parent (Bergen et al, 2006; Frank et al, 2019). Correcting outsiders (e.g., regarding assumptions about the biological parent being primary and/or treating that parent with greater respect) was endorsed by half of participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation